2018
DOI: 10.1038/s41566-018-0216-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light generation from enhanced inelastic electron tunnelling

Abstract: Light emission from biased tunnel junctions has recently gained much attention owing to its unique potential to create ultracompact optical sources with terahertz modulation bandwidth 1-5. The emission originates from an inelastic electron tunnelling process in which electronic energy is transferred to surface plasmon polaritons and subsequently converted to radiation photons by an optical antenna. Because most of the electrons tunnel elastically, the emission efficiency is typically about 10 −5-10 −4. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
161
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 26 publications
(14 reference statements)
2
161
1
Order By: Relevance
“…This gives rise to a so‐called Purcell effect, resulting in the occurrence of additional optical states and, consequently, leading to a significant enhancement of the photon generation (Figure ). Similar effect of the light emission enhancement up to few percent of quantum efficiency has been demonstrated in a recent study with two single‐crystal silver particles . Note that MDM contact under applied bias can also be considered as a compact photosensitive element due to its nanoantenna optical rectification properties .…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This gives rise to a so‐called Purcell effect, resulting in the occurrence of additional optical states and, consequently, leading to a significant enhancement of the photon generation (Figure ). Similar effect of the light emission enhancement up to few percent of quantum efficiency has been demonstrated in a recent study with two single‐crystal silver particles . Note that MDM contact under applied bias can also be considered as a compact photosensitive element due to its nanoantenna optical rectification properties .…”
supporting
confidence: 78%
“…Note, that according to the previous studies, the magnitude of bias related to the abovementioned features corresponds to the regime of efficient photon generation in a tunnel junction. The experimental data in previous studies demonstrate that the maximum light emission efficiency and feature of I ( V ) curve are observed at the same bias. Nevertheless, the authors left the discussion of this phenomenon beyond the scope of their works.…”
mentioning
confidence: 76%
“…1d). The efficiency of IET can be strongly enhanced by a high local density of optical states (LDOS) [20][21][22] . IET offers distinct advantages such as the absence of any active materials resulting in a large bandwidth while offering efficiencies of up to 2% 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Even though quite some effort has already been devoted to optical Yagi-Uda antennas 4 -best possible design parameters have been found for both vertical 5 as well as in-plane emitting antennas 6 and different kinds of antennas have been realized [7][8][9][10][11][12] -the main drawback of the hitherto approaches is that the light is not generated locally but bulky lab-scale setups are needed as excitation sources. Generating light locally at the nanoscale is possible by different means, for example via scanning tunneling microscopes (STMs) 13,14 , carbon nanotubes [15][16][17][18] , quantum dots 19 and optical antennas [20][21][22] . However, obtaining directed electrically driven emission is only possible by utilizing STMs 23,24 , which again involves bulky lab-scale setups, or by twisting the arms of electrically driven dipole antennas in order to break the point symmetry 25 .…”
mentioning
confidence: 99%
“…Until recently, prohibitively low electron‐to‐photon conversion efficiency (10 4 –10 7 electrons result in a single photon14–16,21–23) due to the large momentum mismatch between the initially excited MIM‐TJ cavity mode (MIM‐SPP) and the radiating mode, coupled with an inelastic tunneling event probability of 10%,24 has prevented practical applications of MIM‐TJs. Recently, we have shown that the electron‐to‐SPP conversion efficiency can be experimentally as high as 1% in a planar Al‐AlO x ‐Cr‐Au MIM‐TJ,17 and Qian et al25 demonstrated 2% electron‐to‐photon emission efficiency in a resonant Ag–polymer–Ag nanocrystal tunnel junction, both within one order of magnitude agreement with theoretical inelastic tunneling models,24,26 demonstrating the potential of MIM‐TJs in nano‐scale optoelectronics.…”
Section: Introductionmentioning
confidence: 99%